2005
DOI: 10.1002/pssc.200461570
|View full text |Cite
|
Sign up to set email alerts
|

Rapid synthesis of high purity GaN powder

Abstract: High purity, strong luminescent gallium nitride (GaN) powders were synthesized by direct reaction of gallium (Ga) and ammonia (NH 3 ) using bismuth (Bi) as a catalyst in a vertical furnace. The reaction rate and yield from metal Ga were improved dramatically in the presence of Bi. In this simple apparatus, 25g Ga can be fully, stoichiometrically converted into GaN within 5 hours. The optimum temperature, NH 3 flow rate and reaction time in this hot wall tube furnace were 1000 o C, 500 standard cubic centimetre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The full spectrum including ±1/2 ↔ ±3/2 satellite transitions of the sample prepared using a Na/K flux has been given previously, along with chemical shift referencing, assignments of a minor component from the cubic polytype and spinning sidebands (seen as minor bumps in all three spectra), and additional characterization. Two of the samples were prepared by a new synthetic procedure reacting Ga metal with NH 3 in the presence of Bi catalyst in boats made of either quartz or BN. All samples, especially the two made with Bi catalyst, exhibit a broad structureless absorption on the high frequency (left) side of the main h-GaN peak.…”
mentioning
confidence: 99%
“…The full spectrum including ±1/2 ↔ ±3/2 satellite transitions of the sample prepared using a Na/K flux has been given previously, along with chemical shift referencing, assignments of a minor component from the cubic polytype and spinning sidebands (seen as minor bumps in all three spectra), and additional characterization. Two of the samples were prepared by a new synthetic procedure reacting Ga metal with NH 3 in the presence of Bi catalyst in boats made of either quartz or BN. All samples, especially the two made with Bi catalyst, exhibit a broad structureless absorption on the high frequency (left) side of the main h-GaN peak.…”
mentioning
confidence: 99%
“…3 Results and discussion Some earlier experiments showed that the crystal quality obtained from sublimation growth using commercially available GaN powders are not satisfying which was also reported by Wu et al [5]. Those commercial powders have a yellowish colour and an oxygen content in the range of some percent.…”
Section: Thermogravimetry (Tg) Measurementsmentioning
confidence: 76%
“…One key question in GaN vapor phase growth is whether GaN powder or liquid gallium should be provided as source material. In case of using a GaN powder source for the vapor phase growth the quality and purity of the GaN source material is very important [2]. Therefore, thermogravimetric (TG) measurements are used to investigate the evaporation behaviour of GaN powders.…”
Section: Introductionmentioning
confidence: 99%